Genetic polymorphisms and plasma concentrations of leptin (rs7799039) and adiponectin (rs17300539) are associated with obesity in children and adolescents - Carlos Alberto Menezes; Eduardo Rodrigues Alves Junior; Gustavo Nunes de Oliveira Costa; Thaís Caroline Dallabona Dombroski; Rafael Teixeira de Mattos; Juliana de Assis Silva Gomes; Fabricio Rios-Santos (Sociedade de Pediatria de São Paulo, 2022)
ABSTRACT Objective: The aim of this study was to compare the anthropometric, biochemical, and hormonal characteristics and the presence of genetic polymorphisms of leptin, adiponectin, and tumor necrosis factor alpha (TNF-α) between eutrophic and obese children and adolescents. Methods: This is a case-control study involving 104 children and adolescents. All subjects were assessed for anthropometric characteristics and clinical, laboratory, and genetic polymorphism parameters. The sample was selected from the pediatric endocrinology outpatient clinic specialized in the treatment of obesity in children and adolescents according to the Centers for Disease Control and Prevention (CDC) classification, and controls were selected from the same location in the general pediatric outpatient clinic. Results: As a result, the parameters, such as black color, obese parents, hypertensive parents, and early weaning, were found to be associated with obesity. Increased levels of insulin, triglyceride, total cholesterol, LDL cholesterol, CRP-U, AST, ALT, GGT, free T4, IGF-1, and uric acid and low levels of HDL cholesterol are found to be associated with a higher chance of obesity. The presence of AG/AA polymorphisms in the leptin is associated with a 290% (OR 3.9) higher chance of obesity, and for adiponectin genes, the chances are 740% (OR 8.4) higher. In these obese children and adolescents with AG/AA haplotypes, serum leptin levels were increased and adiponectin levels were decreased in eutrophic individuals, whereas serum TNF-α levels did not change. Conclusions: The AG/AA polymorphisms in the leptin and adiponectin genes alter the serum levels of these adipokines and predispose them to obesity, and many anthropometric, biochemical, and hormonal markers are altered, demonstrating early consequences for the health of these obese children and adolescents.